Selected papers of the Dakar Symposium on Acid Sulphate Soils, Dakar, Senegal, January, 1986: Vol.44 (ILRI, 1988)
The book mentions the presentation of several cases of acid sulphate soil phenomena from upland areas. It innovates in the introduction of geostatistical analysis and improved methods of identifying active and potential acidity. The book also refines on mathematical models that simulate essential processes, and renews the attention for microbiological and plant physiological processes. In adapted research, the book offersthe various papers on pisciculture and forestry as alternatives to the conventional use of acid sulphate soils for rice cultivation and also the papers on the environment and socio-economic aspects of reclamation projects